Development of Cross-Sector Collaboration Indicators for Accelerating the Reduction of Stunting in South Sulawesi, Indonesia - Balqis, Balqis; Suci Rahmadani; Muh. Yusri Abadi; St. Rosmanely; Arif Anwar; Laksmi Trisasmita; Ni Made Viantika Sulianderi; Faizal Fahmi; Arsunan Arsin; Muh. Amri Arfandi; Nur Annisa Hamka; Amaliah Amriani. AS (Journal of Public Health and Pharmacy, 2024)
Background: To reduce stunting, the government of Indonesia, which has the fifth-highest prevalence of stunting in toddlers, launched the National Strategy for the Acceleration of Stunting Prevention (StraNas Stunting). Despite involving multiple sectors, stunting rates remain high. This research aimed to develop cross-sector collaboration indicators to assess the effectiveness of cross-sector efforts in reducing stunting. Method: This qualitative study utilized a rapid assessment procedure (RAP) to generate cross-sector collaboration indicators through in-depth interviews with five key informants and four experts. The recurring themes from these interviews were identified as indicators, which were further refined. In the second phase, quantitative analysis was conducted with 50 respondents to test the developed indicators using Confirmatory factor analysis (CFA) methods. Result: A total of 15 indicators and 41 sub-indicators of cross-sector collaboration were developed across five key dimensions: governance, administration, autonomy, mutuality, and norms. Confirmatory Factor Analysis (CFA) was performed to validate the indicators, with the results showing that the Average Variance Extracted (AVE) for each dimension was greater than 0.5, and the Composite Reliability (CR) exceeded 0.7. These findings confirm the validity and reliability of the developed indicators. Conclusion: As recognized by experts, the theory of cross-sector collaboration has been further advanced by the cross-sector collaboration indicators generated in this study. Additionally, these indicators, which were based on five dimensions of collaboration, may be used to assess cross-sector performance for the Stunting Acceleration Program in Indonesia. The framework of this study for defining and assessing collaboration was expected to provide a foundation for further research.